A Comparative Analysis of Interpupillary Distance and Corneal Diameter for Assessment of Width of Maxillary Central Incisor Using Digital Photography (Journal of Pharmaceutical Negative Results, 2022)
Aim - The purposefulness of this study was to establish if a correlation existed between interpupillary distance, corneal diameter, and the width of the maxillary central incisor in selection of teeth .Materials and methods - A total of 120 subjects-60 males and 60 females in the age group 18-26 years were selected based on predetermined selection criteria. On smiling the digital facial image constituting the teeth and the eyes were captured using standardized digital camera. The digital measurements of the interpupillary distance, corneal diameter (medial aperture height, tangential to cornea) and mesiodistal width of maxillary right central incisor in millimeters were analysed using Adobe Photoshop creative cloud software. The data was tabulated , to assess the association between the variables a Karl Pearson’s Coefficient of Correlation was used.Result –Although the Pearson correlation coefficient(PC) was relatively weak (r<0.39) a significant relationship existed between interpupillary distance and (right, left) maxillary central incisor width with p-value <0.01. A negligible positive correlation (r< 0.27) existed between right corneal diameter and (right, left) maxillary central incisor width with p value <0.01. A negligible positive correlation (r< 0.28) existed between left corneal diameter and (right, left) maxillary central incisor width with p value <0.01.Conclusion - The correlations between interpupillary distance, right and left corneal diameter with maxillary central incisor were unable to produce a strong positive statistical association.